Plant Mites and Sociality Diversity and Evolution - Saito, Yutaka; SpringerLink (Online service) (Tokyo : Springer Japan, 2010)
Mites are very small animals, characterized by wingless and eyeless bodies, in which sociality has been discovered. This book offers detailed descriptions of the diverse social systems and the social evolution of mites, ranging from genetic to ecological aspects. Through a broad spectrum of studies including traditional natural history, taxonomy, modern evolutionary and behavioral ecology, and theoretical models as well, the book addresses a number of important findings on plant mite evolution and species radiation, with the author succeeding in combining theoretical and practical approaches in behavioral ecology by proposing a new game theory. These findings reflect the complex evolutionary history of these taxa and also help to point out clearly what is known and what is not yet known to date. Mites have been considered a minor animal group, but the author shows that mites actually possess great diversity and therefore make unique materials for evolutionary and behavioral studies.
What Are Mites? -- Plant Mites -- Diverse Microcosmos on Sasa -- Mite Sociality -- Inbreeding Depression in Haplo-diploidy -- Kin Selection -- Is Basic Science the Father of Applied Science? -- Further Research for Mite Behavioral and Evolutionary Ecology.
Keywords: Life sciences; Animal behavior; Animal ecology; Evolution (Biology).; Zoology; Life Sciences; Zoology; Animal Ecology; Evolutionary Biology; Behavioural Sciences